Impact of religious values and habit on an extended green purchase behaviour model - Ghazali, Ezlika Mohd; Mutum, Dilip S.; Ariswibowo, Nanang (Wiley, 2018)
Green purchase behaviour is an increasingly important topic, gaining much attention. A review of current literature reveals that the relationship between green attitudes and green purchase behaviour is contentious because consumers’ attitudes do not necessarily translate into green purchase behaviour. This paper examines the relationships between religious values, green habit, and green purchase behaviours via a holistic approach based on the Theory of Reasoned Action and Homer and Kahle's (1988) cognitive hierarchy model. Data were collected from 504 Muslim consumers in two Southeast Asian countries, namely, Indonesia and Malaysia. Partial least squares (PLS), a variance-based structural equation–modelling technique, was selected to test the research model and hypotheses. The term “religious values” is conceptualised in this paper as a multidimensional construct with reflective first-order and formative second-order items. Previous studies have ignored the quest orientation, which refers to constant questioning and doubting as a way of being religious. The results demonstrate that religious values have a positive impact on natural environmental orientation, environmental concerns, green purchase attitudes, and green purchase intentions. Green habit and green purchase intentions were also found to positively affect green purchase behaviours. This study also highlights the important role of habit, namely, a stronger impact on green behaviour than intentions. Green habit was also found to moderate the relationship between green attitudes and green intentions. The study has practical implications for green marketers, green policy makers, and green consumers, as well as directions for future research.